Pelatihan Kreasi Olahan Pangan Lokal Bahan Dasar Tepung Mocaf untuk Pelaku Usaha Kuliner di Jawa Tengah - Ira Handayani; U Yuyun Triastuti; Tri Rettagung Diana; Esteria Priyanti; Ndaru Prasastono (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
The purpose of this training is to make business actors in Central Java have innovation and creativity in maximizing mocaf flour to be used as processed food products. This training was carried out in collaboration with Dinas Ketahanan Pangan Provinsi Jawa Tengah with Program Studi Seni Kuliner Akademi Kesejahteraan Sosial Ibu Kartini. There are 30 participants who took part in this training. The training methods used include lecture methods, practice methods, question and answer methods, and evaluations. The results of the training were in the form of local food products made from mocaf flour in the form of Bomboloni, Dimsum, Risol Mayo, and Sus Vla Buah.